PERNIKAHAN DINI DALAM HUKUM ISLAM: ANTARA TRADISI DAN REALITAS - Risma Cahya Nariti; Niken Amalina Setiyani (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Early marriage is a marriage where a child does not yet have physiological, psychological and financial maturity. Cultural traditions and the environment are one of the causes of early marriage. To be able to prevent this, it is necessary to provide adequate education to the community so that they know how serious a marriage is. Therefore, both the government and the family can contribute to reducing the occurrence of early marriage. In this research, the method used is library research where this research uses sources such as journals, books, and scientific papers that are related to the research topic. The purpose of this study is to provide a deeper understanding of early marriage, causal factors and how to prevent it.